The Frequency Response of a Cavitating Hydrofoil. (September 2014) - Jamalabadi, M.Y. Abdollahzadeh
The frequency response of a hydrofoil such as the rudder and propeller is important for ship equipment design. In the present study the cavitation reaction on a hydrofoil vibrating in a viscous fluid is constructed by superposition of a potential flow solution. An analytic expression for the fluid pressure as a function of cavitation number, ship velocity, and the incidence angle is considered in solid-fluid interaction when solving the equation of motion of the hydrofoil. The first three natural frequencies of the hydrofoil are calculated as a function of the incidence angle, the aspect ratio, the cavitation index, and the free stream velocity. The results show by the increase of the incidence angle and the aspect ratio, and the decrease of the cavitation index, and the free stream velocity, the natural frequencies increased.